Molecular cloning and structural modelling of gamma-phospholipase A2 inhibitors from Bothrops atrox and Micrurus lemniscatus snakes - Picelli, Carina G.; Borges, Rafael J. [UNESP]; Fernandes, Carlos A.H. [UNESP]; Matioli, Fabio M. [UNESP]; Fernandes, Carla F.C.; Sobrinho, Juliana C.; Holanda, Rudson J.; Ozaki, Luiz S.; Kayano, Anderson M.; Calderon, Leonardo A.; Fontes, Marcos R.M. [UNESP]; Stábeli, Rodrigo G.; et al. (Elsevier, 2017)
Phospholipases A2 inhibitors (PLIs) produced by venomous and non-venomous snakes play essential role in this resistance. These endogenous inhibitors may be classified by their fold in PLIα, PLIβ and PLIγ. Phospholipases A2 (PLA2s) develop myonecrosis in snake envenomation, a consequence that is not efficiently neutralized by antivenom treatment. This work aimed to identify and characterize two PLIs from Amazonian snake species, Bothrops atrox and Micrurus lemniscatus. Liver tissues RNA of specimens from each species were isolated and amplified by RT-PCR using PCR primers based on known PLIγ gene sequences, followed by cloning and sequencing of amplified fragments. Sequence similarity studies showed elevated identity with inhibitor PLIγ gene sequences from other snake species. Molecular models of translated inhibitors' gene sequences resemble canonical three finger fold from PLIγ and support the hypothesis that the decapeptide (residues 107–116) may be responsible for PLA2 inhibition. Structural studies and action mechanism of these PLIs may provide necessary information to evaluate their potential as antivenom or as complement of the current ophidian accident treatment.
Keywords: Bothrops atrox; Gamma type phospholipase A2 inhibitors; Inhibitors of phospholipases A2; Micrurus lemniscatus; Snakes